BRAND IMAGE AND ISLAMIC MARKETING AS DETERMINANTS OF PURCHASING DECISIONS FOR BOTTLED DRINKING WATER PRODUCTS - Nur Sayfudin; Finny Ligery; A. Muslimin (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study aims to analyze the effect of brand image and Islamic marketing on purchasing decisions of Way NU bottled drinking water products in Metro City, both partially and simultaneously. The scope of this research focuses on consumer behavior in making purchasing decisions influenced by branding factors and Islamic values. This study employs a quantitative approach with an explanatory research design. The sample consists of 100 respondents selected using purposive sampling, with criteria of being at least 17 years old and having purchased Way NU products. Data were collected through questionnaires using a Likert scale and analyzed using validity, reliability, normality, and linearity tests, as well as multiple linear regression analysis with the assistance of IBM SPSS Statistics 25. The results show that brand image has a positive and significant effect on purchasing decisions with a significance value of 0.039. Islamic marketing also has a positive and significant effect with a significance value of 0.000 and is the more dominant variable. Simultaneously, both variables significantly influence purchasing decisions, as indicated by an F-value of 107.581 and a significance level of 0.000. The coefficient of determination (R²) of 0.689 indicates that 68.9% of the variation in purchasing decisions can be explained by brand image and Islamic marketing. In conclusion, marketing strategies that integrate strong brand image and Islamic marketing values are effective in increasing consumer purchasing decisions, particularly in communities with high levels of religiosity